The diagnostic imaging of autoimmune pancreatitis - A. B. Luk’yanchenko; Th. C. Lauenstein; K. A. Romanova (Вестник рентгенологии и радиологии)
The current approaches to diagnosis of autoimmune pancreatitis, а form of IgG4-related disease, are being discussed. The pathology, clinical presentation and radiological features of different imaging modalities (CT, MRI) have been described. Difficulties of differential diagnosis of autoimmune pancreatitis with some malignant tumors are reviewed.